2016
DOI: 10.1016/j.automatica.2015.11.021
|View full text |Cite
|
Sign up to set email alerts
|

An internal model approach to (optimal) frequency regulation in power grids with time-varying voltages

Abstract: This paper studies the problem of frequency regulation in power grids under unknown and possible time-varying load changes, while minimizing the generation costs. We formulate this problem as an output agreement problem for distribution networks and address it using incremental passivity and distributed internal-model-based controllers. Incremental passivity enables a systematic approach to study convergence to the steady state with zero frequency deviation and to design the controller in the presence of time-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
325
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 164 publications
(325 citation statements)
references
References 44 publications
0
325
0
Order By: Relevance
“…Similar to [38,Remark 5] it can be shown that if the assumption above is satisfied then necessarily V ∈ R N >0 . Furthermore, in case the network is a tree, it is easy to observe that (52) is satisfied if and only if there exists V ∈ R N >0 such that…”
Section: Attractivity Of the Synchronous Solutionmentioning
confidence: 92%
See 2 more Smart Citations
“…Similar to [38,Remark 5] it can be shown that if the assumption above is satisfied then necessarily V ∈ R N >0 . Furthermore, in case the network is a tree, it is easy to observe that (52) is satisfied if and only if there exists V ∈ R N >0 such that…”
Section: Attractivity Of the Synchronous Solutionmentioning
confidence: 92%
“…Another way, is to express the dynamics of the system using directly (η, ω, V ) variables, similarly as in [38]. However, we do not adopt this approach here in order to better contrast our results with others in the literature on oscillator synchronization that are mostly working with (θ, ω, V ) coordinates [14], [32], [27], [20].…”
Section: Remarkmentioning
confidence: 99%
See 1 more Smart Citation
“…evolve on the circle), the corresponding Lyapunov function of [3], [4] has also to be periodic, which is a severe requirement. Paramount examples of such systems are the forced nonlinear pendulum [17], [19], power systems [32], [35], [43], [44], microgrids [36], [42], phase-locked loops [25], [26], and complex networks of oscillators [40], [12], [41].…”
Section: Introductionmentioning
confidence: 99%
“…in [14]. However, the swing equations are inaccurate and only valid on a specific time scale up to the order of a few seconds so that asymptotic stability results are often invalid for the actual system [2], [6], [8].…”
Section: Introductionmentioning
confidence: 99%